Unity and Plurality in Songs of Almajiri: An Anthology of Poems in Almajirci - Mohammed, Hajara Bk (Research in African literatures, 2025)
The issue of Al-Majirci in northern Nigeria has garnered considerable attention from scholars, writers, and critics. However, existing research lacks a thorough exploration of its literary underpinnings. This paper uses postcolonial theory as its lens and polyphony as its methodology to investigate the extent to which cultural studies is an appropriate and effective channel for elucidating human experiences such as that of the Al-Majiri child scholar in Songs of AlMajiri. This approach allows readers to engage with a harmonious convergence of diverse sensory experiences—tastes, smells, sights, sounds, and emotions—integral to the Al-Majiri’s life through the multitude of voices and perspectives presented. The paper underscores the dual role of literature, not only as a reflective mirror of societal concerns but also as a powerful tool capable of questioning and reshaping them.